Learning-based monocular vision obstacle detection and avoidance for UAV navigation in urban airspace - Zhang, Yuhang (Nanyang Technological University, 2023)
Unmanned aerial vehicles (UAVs), also known as drones, have gained considerable interest among academics in recent years, which significantly increases the demand for autonomous navigation systems for UAVs. In this study, autonomous navigation is addressed as a two-stage problem. The first stage is the obstacle detection phase, during which the UAVs leverage their onboard sensors to perceive the surroundings and detect obstacles. The second stage is the obstacle avoidance phase, where the UAVs make decisions to continue operations without colliding with anything while approaching the target.